2022
DOI: 10.1002/aenm.202203254
|View full text |Cite
|
Sign up to set email alerts
|

Inducing the Preferential Growth of Zn (002) Plane for Long Cycle Aqueous Zn‐Ion Batteries

Abstract: If the preferred growth planes are ( 105), (103), and (002), the crystal grows at an angle of 0-30° from the substrate. If the preferred growth planes are ( 101), ( 102), (112), and (114), the crystal grows at an angle of 30-70° from the substrate. And if the preferred growth planes are ( 100) and ( 110), the crystal grows at an angle of 70-90° from the substrate. [10] By density functional theory (DFT) calculation, Zhu et al. [11] revealed that the binding energies between Zn atom and the (002), (100), and (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
76
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(78 citation statements)
references
References 47 publications
(91 reference statements)
1
76
1
Order By: Relevance
“…28 Li et al recently reported that the preferential adsorption of 1-butyl-3-methylimidazolium cations on the (100) and (101) planes of Zn anodes forces Zn 2+ ions to deposit on the (002) plane, thus leading to the preferential growth of the (002) plane. 29 Despite their great progress, the cycle life of Zn anodes varies greatly depending on the selected electrolyte additives. The reason behind this phenomenon is of significance to guide the design of effective EDL structure regulators but is poorly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…28 Li et al recently reported that the preferential adsorption of 1-butyl-3-methylimidazolium cations on the (100) and (101) planes of Zn anodes forces Zn 2+ ions to deposit on the (002) plane, thus leading to the preferential growth of the (002) plane. 29 Despite their great progress, the cycle life of Zn anodes varies greatly depending on the selected electrolyte additives. The reason behind this phenomenon is of significance to guide the design of effective EDL structure regulators but is poorly understood yet.…”
Section: Introductionmentioning
confidence: 99%
“…[18b] A profound polarization process of CO 2 on the negatively electrified NDSTC surface is thus deduced. [18a,41] The pyrinidic nitrogen is nucleophilic with lone pair electrons while [EMIM] + behaves as electrophile via the C(2)-H. [54] The steric hindrance analogical to weak frustrated Lewis pairs thus creates an active region for the adsorbed CO 2. [37,52a,55] The electron-delocalized pyridinic nitrogen triggers the charge redistribution in CO 2 and the increased electron density in CO 2 oxygen atoms further induces hydrogen-bonding-like interactions with the C(2)-H. [55] The bonding and antibonding orbitals of adsorbed CO 2 thus interact with the unoccupied orbitals of electrophile and non-bonding orbitals of the nucleophile, respectively, leading to the polarization of CO 2 molecules.…”
Section: Elucidation Of Anomalous Edl Structures In Ndstc-il+co 2 Devicementioning
confidence: 99%
“…Organic small molecules are used not only as co-solvents, but also as functional additives in aqueous electrolytes for ZIBs. Their working mechanisms include regulating Zn deposition by absorbing on the surface of Zn anode, breaking the original H-bonds and/or in situ construction of SEI by participation of solvation structures of Zn 2+ [18,65,[70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88][89]. In this section, we mainly focused on the manipulation of solvation structures by adoption of functional additives.…”
Section: Organic Small Moleculesmentioning
confidence: 99%